The Case Against Speciesism and Sexism: An Interactionist Approach to Singer and Adams - Gaylord, Kelsey (Stance: an international undergraduate philosophy journal, 2022)
Using the interactionist approach of comparative philosophy, I evaluate the intersecting points made in Animal Liberationby Peter Singer and The Sexual Politics of Meat: A Feminist-Vegetarian Critical Theory by Carol Adams. The purpose of this paper is to examine how a combination of the utilitarian and feminist perspectives helps us adopt a new philosophy accounting for all systems of oppression involved in eating animals. I conclude that by removing unnecessary harm to animals and unlearning phrases with an absent reference to oppressed groups, society can progress toward an anti-oppressive system of liberation.